El procesamiento y tipificación de delitos contra la propiedad realizados por adolescentes en el código penal. - SUÁREZ PALACIO, HERNÁN VINICIO (2010)
The topic of juvenile delinquency is of recurrent character, it appears and disappears on the political and social agenda with relative easiness. For this reason it is worthwhile to ask about the reasons that explain and permit its high level of manipulation. Constitutionally the Ecuadorian State guarantees the validity of an over protective norm towards adolescents, and parallelly it makes an allusion to the duty of the State, to promote and to guarantee a process of more agile justice and specialized in a concrete case of having been victim of an illicit act, this constitutes the ideal thing of all states entity linked to the administration of justice, because it is an unquestionable obligatorily and a purpose of all government assuring to the whole society the orderliness and correct administration of justice for all, sanctioning severe and correctly those who constitute an eminent danger for society. In the Constitution of 1998, the Penal Code and the Code of Childhood and Adolescence prohibits the imputability and penal responsibility to the offender adolescent; the current constitution does the same thing by protecting the adolescent, nevertheless the current levels of delinquency are much higher and more diverse that in the times when the laws were in force. I can mention some Articles that I consider to be pertinent: Code of Childhood and Adolescence, Article 305 "The adolescents are not processed penally and, therefore, they won't be evaluated by ordinary penal judges and neither the sanctions in the penal laws will apply to them"1 1CODIGO DE LA NIÑEZ Y ADOLESCENCIA, publicado por Ley No. 100. En Registro Oficial 737 de 3 de Enero del 2003, en San Francisco de Quito, Art. 306 textually expresses "The adolescents that execute infractions typified in the penal law will be subject to socio-educational measures for their responsibility in agreement with the precepts expressed in the same Code.”2 Overall, my proposal resides in the faculty of being able to give the adolescent a penal treatment, since in the punishments applied at the moment imposed instead of eradicating juvenile violence, robberies, thefts, and other related crimes. Taking into account their maturity seems to increase, leaving us with a lot to think about of our justice system. It is also necessary to take into account the many mafias or gangs that exist behind juvenile delinquency that take advantage of the adolescents’ juridical situation, of our new constitution, of human rights, etc. to keep using them to make illicit acts and to foment in those young minds the easy life and the social irresponsibility that it bears. To conclude, if in our constitution the facultative vote has been determined, why not giving the adolescent a penal responsibility.